Web based yogyakarta food recipe application using sdlc waterfall method - Annisaa Utami; Dasril Aldo; Yohani Setiya Rafika Nur; Trihastuti Yuniati (Institute of Computer Science (IOCS), 2023)
Cooking is the process of processing food ingredients and seasonings to be used as a variety of dishes. Cooking can be done by anyone. When cooking, recipes are needed as a reference to process food ingredients into a dish. A recipe in the modern sense is defined as a set of instructions that tell how to prepare and cook food, including a list of what foods are needed . Yogyakarta has a variety of culinary delights. With the passage of time, Yogyakarta's specialties are displaced by foreign food entering Yogyakarta. The Recipe application contains a variety of recipes for typical Yogyakarta food. This research aims to help the community in making Indonesian culinary food, especially the Yogyakarta food menu. The application is created web-based using PHP programming language and mysql database. For the software development method, which is carried out is using the Software Development Life Cycle (SDLC) Waterfall method. The first stage carried out is planning, design stages, implementation and trials. Based on the test results using a black box, the system created has functional features according to what is expected. The system features login, Manage recipe data, Manage category data and Manage comment data.